Properties of metal silicides - Maex, Karen; Rossum, Marc van (IEE : INSPEC, 1995)
Annotation The properties of silicon alloyed with metals are presented here for silicides of both transition and rare earth metals.
On title page: IEE.
Keywords: Silicides.; Electronic circuits.; elektronické knihy; electronic books